2004
DOI: 10.1073/pnas.0307578101
|View full text |Cite
|
Sign up to set email alerts
|

Close agreement between the orientation dependence of hydrogen bonds observed in protein structures and quantum mechanical calculations

Abstract: Hydrogen bonding is a key contributor to the exquisite specificity of the interactions within and between biological macromolecules, and hence accurate modeling of such interactions requires an accurate description of hydrogen bonding energetics. Here we investigate the orientation and distance dependence of hydrogen bonding energetics by combining two quite disparate but complementary approaches: quantum mechanical electronic structure calculations and protein structural analysis. We find a remarkable agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
236
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(255 citation statements)
references
References 48 publications
11
236
3
1
Order By: Relevance
“…This energy is a linear combination of four terms that are parameterized by using a set of high-resolution protein crystal structures: (i) distancedependent energy term derived from the distribution of distances between the hydrogen and acceptor atoms (distances range from 1.4 to 2.6 Å), (ii) angular energy measuring angle at Native-like average Z score (top portion of the table), Pearson's correlation coefficient between rmsd and energy score (bottom portion of the table), for low-rmsdnat vs. low-score4ext and low-rmsdext vs. low-score4ext the hydrogen atom, (iii) angular energy measuring angle at the acceptor atom, and (iv) dihedral angle term corresponding to rotation around the acceptor-acceptor base bond in the case of an sp 2 hybridized acceptor (21). It has also been shown that this knowledge-based hydrogen-bonding potential in Rosetta is consistent with the quantum mechanical calculations unlike molecular mechanics force fields, including CHARM27, OPLS-AA, and MM3-2000 (22). Recently a modified version of Rosetta's hydrogen bonding potential was successfully used for protein structure refinement of homology models (23).…”
Section: Differences In Top Clustermentioning
confidence: 70%
“…This energy is a linear combination of four terms that are parameterized by using a set of high-resolution protein crystal structures: (i) distancedependent energy term derived from the distribution of distances between the hydrogen and acceptor atoms (distances range from 1.4 to 2.6 Å), (ii) angular energy measuring angle at Native-like average Z score (top portion of the table), Pearson's correlation coefficient between rmsd and energy score (bottom portion of the table), for low-rmsdnat vs. low-score4ext and low-rmsdext vs. low-score4ext the hydrogen atom, (iii) angular energy measuring angle at the acceptor atom, and (iv) dihedral angle term corresponding to rotation around the acceptor-acceptor base bond in the case of an sp 2 hybridized acceptor (21). It has also been shown that this knowledge-based hydrogen-bonding potential in Rosetta is consistent with the quantum mechanical calculations unlike molecular mechanics force fields, including CHARM27, OPLS-AA, and MM3-2000 (22). Recently a modified version of Rosetta's hydrogen bonding potential was successfully used for protein structure refinement of homology models (23).…”
Section: Differences In Top Clustermentioning
confidence: 70%
“…Hydrogen bond free energy 5,24 relying on the distribution of hydrogen bond rotations within each cluster could be readily implemented as Boltzmann statistics based on HQ60 for example. Coupled to chord diagrams with chords labelled by cluster and the backbone labelled by amino acids, this could provide a new tool for ab initio protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…As the geometric phase space of hydrogen bonds has large dimension a priori, 3D and 4D simplifications have captured only part of their geometry 5,6 . Here, we introduce a systematic 3D descriptor of main chain hydrogen bond geometry by assigning to each hydrogen bond between backbone C ¼ O and N-H atoms a spatial rotation, which is evidently independent of the overall spatial orientation of the protein just as for dihedral angles.…”
mentioning
confidence: 99%
“…Baker & Hubbard (1984) [18,19] found that 90% of analysed NH --O hydrogen bonds in the PDB structure data bank have bond angles about 158 o , and most analysed C=O -H hydrogen bonds have angles about 129 o . Morozov (2004) [20] in a later examination of the high resolution X-ray PDB data bank found the average bond angle for single hydrogen bonds was around 110-120 o . The extent of these errors in the X-ray structures and their effect on calculated binding energies is unknown, and may be large if configurational or molecular geometry distortions are also present.…”
Section: Introductionmentioning
confidence: 99%